ปัญหาและอุปสรรคในการถ่ายโอนสถานีอนามัยให้แก่องค์กรปกครองส่วนท้องถิ่นในเขตอำเภอเมืองลำพูน - โอวาท ทาใจ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The study “Problems and Obstacles in the Transferring of Public Health Center to Subdistrict Administrative Organization in Mueang, Lamphun District” aimed to 1) examine the problems and obstacles in the transferring of public health centers to subdistrict administrative organizations in Mueang, Lamphun District and 2) find out possible solutions to these problems and obstacles as well as ways to appropriately and effectively transfer the public health centers to the subdistrict administrative organizations. This qualitative research employed the documentary research and interview methods. In addition, an open-ended in-depth interview method was conducted with the administrators from Lamphun Public Health Office, subdistrict health centers/hospitals, and subdistrict administrative organizations. Also a semi-structured method was conducted with officials from the health divisions at local administrative organizations and subdistrict health centers/hospitals. Moreover, descriptive analysis was used to analyze the data. The data revealed that there are 5 main problems and obstacles in the transferring of public health centers to subdistrict administrative organizations in Mueang, Lamphun District. First of all, the central policies were not clear especially the Ministry of Public Health, as the transferor, paid more attention to the regional health networks than the transferring of public health centers to subdistrict administrative organizations. Secondly, the budgets allocated by the central government supporting the local administrative organizations did not follow the decentralization plans and procedures. The third problem was the administrators and officials at local administrative organizations were lack of understanding about the transferring of public health centers to subdistrict administrative organizations. Furthermore, most of the subdistrict administrative organizations in Mueang, Lamphun District were small to medium size organizations causing the administrators to focus more on the development of the basic infrastructure mission. Finally, the administrators and officials from the public health centers/hospitals were worried and did not trust the administrators from the local administrative organizations because these administrators were lack of public health knowledge. They also did not trust the budget management which might involve corruptions. Consequently, these administrators and officials did not want to be transferred to the local administrative organizations. Followings are possible solutions to the problems and obstacles in the transferring of public health centers to subdistrict administrative organizations in Mueang, Lamphun District. 1. The government should quickly allocate the budgets for the local administrative organizations according to the designated decentralization plans. 2. The Ministry of Public Health and the local administrative organizations should cooperate in the operation of the transferring the public health centers and establish the job security preparing for the transferring of the officials from the public health centers to the local administrative organizations. 3. The officials from the local administrative organizations and the public health centers should be educated about the transferring of the public health centers for a more effective transfer. 4. The government should encourage the public to participate in monitoring the transfer after the transfer process has completed. 5. The government should allow the local administrative organizations to freely manage their own organizations according to the decentralization plans to effectively provide the benefits for the local people.